Effect of Service Training On Drill Methods And Target Methods On Improving Service Skills For Volleyball - Ruslan, Ruslan; Sandy, Gilberd; Nurjamal, Nurjamal; Ismawan, Hendry (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine the effect of service training on the drill method and the method of using targets on improving service skills for volleyball athletes at Gajah Mungkur Club of Â Samarinda. This type of research is an experiment with descriptive statistical test techniques, inferential statistics, normality tests, homogeneity, and percentage improvement. The population of this study was all female athletes at the Gajah Mungkur Club of Samarinda. Sampling using saturated sampling technique, which is divided into 2 groups, namely drill practice and practice using targets, each group consists of 13 people so that the total number of samples in this study amounted to 26 people. The results showed that there was an effect of the drill method training and the method using the target on the top service results for the athletes of Gajah Mungkur Club of Samarinda which obtained a significant t value = 0.028 <t statistic = 0.05 with a percentage increase of = 33.98%. There is a difference in the effect of the drill method training, which has a value of = 0.360 belonging to the moderate category, and the training method using the target which is obtained by the value = 0.260 belonging to the low category on the top service results of the athletes of the Gajah Mungkur Club of Samarinda. The conclusion is that there is a significant effect of service training on the drill method and the target method on improving service skills for volleyball for the Gajah Mungkur club athletes of Samarinda.